Species-specific profiles and risk assessment of perfluoroalkyl substances in coral reef fishes from the South China Sea. (January 2018) - Pan, Chang-Gui; Yu, Ke-Fu; Wang, Ying-Hui; Zhang, Rui-Jie; Huang, Xue-Yong; Wei, Chao-Shuai; Wang, Wei-Quan; Zeng, Wei-Bin; Qin, Zhen-Jun
Abstract: The contamination profiles of sixteen perfluoroalkyl substances (PFAS) were examined in coral reef fish samples collected from the South China Sea (SCS) where no information about this topic was available in the literature. The results revealed that six PFAS were found in coral reef fish samples from the SCS. Perfluorooctane sulfonate (PFOS) was the most predominant PFAS contaminant detected in most of the samples, with the highest concentration value of 27.05 ng/g wet weight (ww) observed in Cephalopholis urodelus . Perfluoroundecanoic acid (PFUnDA) and Perfluorotridecanoic acid (PFTrDA) were the second and third dominant PFAS, respectively. Mean PFOS concentrations in muscle of seven coral reef fish varied from 0.29 ng/g ww in Lethrinus olivaceus to 10.78 ng/g ww in Cephalopholis urodelus . No significant linear relationship was observed between PFOS levels and coral reef fish traits (length, weight) collected in this region. Average daily intake of PFOS for the seven coral reef fishes ranged from 0.79 ng/kg/d for Lethrinus olivaceus to 29.53 ng/kg/d for Cephalopholis urodelus . The hazard ratio (HR) values for human consumption of PFOS-contaminated coral reef fishes ranged from 0.04 to 1.48, with Cephalopholis urodelus having the highest HR value of 1.18 (higher than 1) among the species, indicating frequent consumption of Cephalopholis urodelus might pose potential health risk to local population. The present work have provided the first hand data of PFAS in coral reef fishes in the SCS and indirectly demonstrated the existence of low level PFAS pollution in the SCS in China. Graphical abstract: Image 1 Highlights: First comprehensive investigation of PFASs in coral reef fishes. PFOS was the predominant PFAS found in coral reef fishes from South China Sea. PFOS concentrations in coral reef fishes up to 27.05 ng/g wet weight. Odd chain PFCA had higher ratios versus the corresponding shorter even-chain PFCA. Frequent consumption of Cephalopholis urodelus may pose health risk.